The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1007/s11604-008-0234-y
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo study on a flattening filter-free 18-MV photon beam of a medical linear accelerator

Abstract: Our study showed that the increase in dose rate and lower out-of-field dose can be possible advantages for an unflattened 18-MV beam.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 11 publications
(22 reference statements)
1
16
0
Order By: Relevance
“…Physical and dosimetric differences between standard FF and unflattened FFF beams have been analyzed by various groups both through measurements and/or using Monte Carlo simulations on modified or clinically available linacs. The main issues are summarized in the paper from Georg et al 4 They rely mainly on general beam characteristics, [5][6][7][8][9][10][11][12][13][14] spectrum, beam energy and depth doses, [15][16][17][18] backscatter, 19 electron contamination, 20 out of field dose, 10,11,20,21 neutron production, 20,22,23 and shielding requirements. 24,25 Standardized and consolidated beam parameters as described or referenced in, for example, AAPM TG 142, 26 are used today for the quality assurance of flat photon beams, e.g., flatness, symmetry, and penumbrae.…”
Section: Introductionmentioning
confidence: 99%
“…Physical and dosimetric differences between standard FF and unflattened FFF beams have been analyzed by various groups both through measurements and/or using Monte Carlo simulations on modified or clinically available linacs. The main issues are summarized in the paper from Georg et al 4 They rely mainly on general beam characteristics, [5][6][7][8][9][10][11][12][13][14] spectrum, beam energy and depth doses, [15][16][17][18] backscatter, 19 electron contamination, 20 out of field dose, 10,11,20,21 neutron production, 20,22,23 and shielding requirements. 24,25 Standardized and consolidated beam parameters as described or referenced in, for example, AAPM TG 142, 26 are used today for the quality assurance of flat photon beams, e.g., flatness, symmetry, and penumbrae.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of studies have relied on Monte Carlo methods for the investigation of FFF beam characteristics; [13][14][15][16][17] with regard to direct measurements and commissioning, the majority of works have described the properties of linear accelerators of the Varian and Elekta types. [18][19][20][21][22][23] Only very few centers worldwide have so far, to our knowledge, worked with FFF Siemens accelerators, and information on the dosimetric properties is not yet available.…”
Section: Introductionmentioning
confidence: 99%
“…34,35 Removal of flattening filters from linacs has been proposed and studied in several investigations as a way to increase the dose rate for radiosurgery and intensity-modulated radiation therapy (IMRT) treatments. 25,[36][37][38][39][40] It was shown that neutron fluence for a 18 MeV beam of Varian linac was about 69% lower for a flattening filter free beam measured by gold foil activation in neutron moderators. 39 Another MC study by Mesbahi on Elekta SL-25 showed results very close to those of a Varian linac.…”
Section: Photoneutron Production In Linac Headmentioning
confidence: 99%